2009
DOI: 10.2143/ac.64.3.2038029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of rosuvastatin therapy and percutaneous coronary intervention on angiogenic growth factors in coronary artery disease patients

Abstract: There is an elevation of VEGF levels early after myocardial revascularization that may reflect a transient ischaemia and potentially may provoke atherosclerotic plaque neovascularization. Rosuvastatin leads to a decrease of VEGF levels that can be a reflection of the influence on endogenous angiogenesis. There was no correlation between inflammatory factors and VEGF that gives a suggestion about an absence of direct CRP and IL-6 impact on VEGF decreasing during statin treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Several authors have shown that IL-6 overexpression could lead to a commercial application for therapeutic angiogenesis, because of enhanced neovascularization in ischemic diseases. 29,30 IL-6 may induce angiogenesis in blood vascular ECs via increased TGF-β1-mediated endogenous production of angiogenic growth factors. The observed increase in angiogenesis of blood vascular ECs may in turn promote the proliferation of FBs.…”
Section: Il-6 Promotes Myocardial Fibrosis J-h Wang Et Almentioning
confidence: 99%
“…Several authors have shown that IL-6 overexpression could lead to a commercial application for therapeutic angiogenesis, because of enhanced neovascularization in ischemic diseases. 29,30 IL-6 may induce angiogenesis in blood vascular ECs via increased TGF-β1-mediated endogenous production of angiogenic growth factors. The observed increase in angiogenesis of blood vascular ECs may in turn promote the proliferation of FBs.…”
Section: Il-6 Promotes Myocardial Fibrosis J-h Wang Et Almentioning
confidence: 99%
“…Statins are HMG-CoA reductase inhibitors that can reduce the synthesis and secretion of intracellular cholesterol, facilitate serum cholesterol removal, and inhibit the synthesis of apolipoprotein [ 29 ]. The effect of statins has been recognized in the prevention of coronary heart disease [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly there are studies proving that statin treatment can reduce VEGF levels in serum as well as atherosclerotic plaque volume [107,108]. In a study using statins and more specifically fluvastatin, in a mouse model demonstrated that statin treatment can have beneficial effects by inhibiting the up-regulation of angiogenic molecules such as VEF, HIF-1α and phospho-STAT3.…”
Section: Statins For Treating Pathological Angiogenesismentioning
confidence: 99%